1984
DOI: 10.1073/pnas.81.13.3954
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a chicken embryonic globin gene in adult erythroid cells by 5-azacytidine and sodium butyrate.

Abstract: Adult White Leghorn chickens were rendered anemic by injection with 1-acetyl-2-phenylhydrazine and then treated with parenteral 5-azacytidine, and levels of embryonic globin RNA in circulating reticulocytes were measured. A very small but detectable amount of correctly initiated embryonic p-type globin RNA was detected in reticulocytes from birds treated with 5-azacytidine, while none was detected in reticulocytes from those receiving only phenylhydrazine or phenylhydrazine plus 1-f3-D-arabinofuranosylcytosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 41 publications
2
81
0
Order By: Relevance
“…There is evidence that sodium butyrate may act at the transcription level by increasing the acetylation of histones, thereby releasing constraints on the DNA template and reactivating a number of genes (25,26). Sodium butyrate also increases the expression of fetal-globin genes in adult baboons, humans, and other animals (27)(28)(29). In utero infusions of butyrate delay the developmental switch from ␥-to ␤-globin gene expression in sheep fetuses (29).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that sodium butyrate may act at the transcription level by increasing the acetylation of histones, thereby releasing constraints on the DNA template and reactivating a number of genes (25,26). Sodium butyrate also increases the expression of fetal-globin genes in adult baboons, humans, and other animals (27)(28)(29). In utero infusions of butyrate delay the developmental switch from ␥-to ␤-globin gene expression in sheep fetuses (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of haemoglobinopathies, utero infusions of Butyrate, delay the developmental switch off γ to β-globin gene expression in sheep fetuses (32). Sodium butyrate and similar derivatives increases the expression of fetal-globin genes and are being used clinically in treatment of β-Thalassemia and sickle cell anemia (23,24,33). These effects of butyrate may occur through the inhibition of histone deacetylase (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In hemoglobinopathies, Butyrates are clinically used to treat sickle-cell anemia and Thalassemia through induction of the expression of γ-gene, producing fetal hemoglobin (HbF) and activating the γ-globin (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Butyrate was shown to promote cell differentiation and to enhance globin gene expression in human erythroleukemia cells [124], to increase embryonic globin gene expression in chicken adult erythroid cells pretreated with 5-azacytidine [125], to cause higher HbF levels at birth in infants born from diabetic mothers (infants of diabetic mothers have a delay in γ to β globin switch after birth associated with elevated plasma α-amino butyric acid levels) [126,127], to enhance HbF synthesis in cultures of primary adult erythroid progenitors/precursors [128], and to increase HbF synthesis in adult baboons [129,130]. Furthermore, it was shown that butyrate infusions in the ovine fetus delay the switch from fetal to adult hemoglobin [131].…”
Section: Butyratementioning
confidence: 99%